Em nome do pai, da mãe e dos filhos: a (des)ordem da família e suas regulações educacionais nos discursos pastorais da igreja católica - Santos, Cícero Edinaldo dos (2019)
It has the objective to understand the (re)signification of the order of the family in the pastoral speeches of the Catholic Church, from pontifical and council documents, widespread internationally between the XIX and XX centuries available in the Vatican’s website. It intends to identify the framework from the family’s order in the Catholic Church’s pastoral speech, as well as its changes and permanences in this long historical juncture, emphasizing its interface with the home education. Its epistemological affiliation is the historical-comparative studies in education. Prioritizes the qualitative approach and interdisciplinary dialog. It uses the foucaultian principles of pastoral speeches analysis (inversion, discontinuity, exteriority and specificity). It goes from the hypothesis in which the Catholic Church’s pastoral speech had the desire to promote the obedience for the fulfillment of the promise of salvation, i.e. an eternal life, after death. These pastoral speeches delimited existence ways with the Marriage sacrament. In the face of the growth of the secularization, joined and after political alterations, socioeconomics and cultural, the pastoral speeches presented education regulations for the maintenance of the longed order, as to maintain it in the future generations. The family became a target and an environment of its order itself. It considers that the pastoral speeches of the Catholic Church are influenced by three driving bases: the Sacred Scripture, the apostolic Tradition and the Teaching of the Church. The order of the family is put between two antagonistic poles: comitting sins of the flesh and the obedience for the fulfillment of the promise of salvation. It has as a central column the sacrament of Marriage, made by a man and a woman, with consent from both. The Marriage, in turn, is grounded in three main presuppositions: the indissolubility of the union, the conjugal loyalty and the procreation. To bring this order into effect, home education has effective importance, because the father and the mother are considered the first educators of the children. During the process of resignification of the family's order, these enunciative systems were reiterated and reactivated. The pastoral speeches intended to maintain the longed order in the future generations, turning the family into an active education institution. They stimulated the honor, the chastity example and the preventive vigilance at home, “in the name of the father, the mother and the children”.